PENGARUH NON PERFORMING LOAN, CAPITAL ADEQUACY RATIO, DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS BANK YANG TERCATAT DI BURSA EFEK INDONESIA - Lasty Agustuty D (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This study was conducted to examine the effect of variable Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) to Return on Assets (ROA). The sampling technique used is purposive sampling with criteria of commercial banks in Indonesia which presents the financial statements of the period 2010 to 2013. The data obtained by the publication of the Indonesian Banking Directory of the period 2010 to 2013. Obtained a total sample of 15 companies from 25 commercial banks in Indonesia 2010- 2013 period. Analysis techniques that will be used in this research is multiple linear regression to obtain a comprehensive picture of the relationship between the variables and the other variables. During the observation period LDR and CAR show a significant positive effect on ROA, while NPL significantly negative effect on ROA. This suggests that the Bank should focus more on NPL problems that can increase the profitability of the bank. The result is expected that the variable Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) can be used as guidelines, either by the management company in the management of the company, as well as by investors in determining investment strategy.